PENGARUH APLIKASI BIOCOCOTIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PADA TANAH PASIR PESISIR PANTAI - Anandyawati Anandyawati; Merlian Zikri; Eko Sumartono; Ridha Rizki Novanda; Amir Husaini Karim Amrullah; Ari Anggoro (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2020)
The great potential in coastal sandy lands is followed by various problems and limiting factors that cause the acceleration of land use for agricultural purpose run very slowly. To overcome these limiting factors, appropriate modification and implementation of innovation is needed, namely the providing of soil conditioning materials, such as organic matter. One source of organic material that is still very rarely used, affordable, easy and cheap and simple in its application is the waste of coconut powder and human waste which we call biococotin. Providing of biococotin in coastal sandy lands decreases basic pH near neutral, increasing levels of N, P, K, C-Organic and cation exchange capacity has decreased from 7.20 to 6.40%. N levels increased from 0.021% to 0.17%, P-available increased from 2.52 ppm to 20.13 ppm, K levels increased from 2.52 cmol (+) to 9.35 cmol (+) and CEC increased from 4, 04 cmol (+) / kg becomes 7.07 cmol (+) / kg. The best growth parameters (plant height, number of leaves, longest leaf length and longest leaf width) are shown by treatment 2 which is half the dose of NPK and biococotin. The best average planting weight and yield per ha is shown by treatment 2, which is half the dose of NPK and biococotin, which is 44.03 grams / plant and 26.41 tons / ha bicocotin. Keywords : Biococotin, Coastal area, Cocopeat